EFFECTIVENESS OF SURFACTANTS AS A COMPOUND FORM FORMULATION OF BIODISPERSANTS AND ITS POTENTIAL APPLICATIONS AS OIL SPILL RESPONSE AGENTS - Dwi Pambudi, Rafi
Oil spill that occur offshore is caused by various activities, including loading and unloading of ships and tankers loaded with oil. This causes damage to the aquatic environment because it can cause the formation of a thin layer on the surface of sea water so that light penetration is blocked and inhibits the process of photosynthesis in sea water. Sophorolipid as an oil spill response agent will be mixed with other surfactant compounds to form a biodispersant formulation design in this study. The first mixture of Sophorolipids (biosurfactants) and chemical dispersants (Methyl Ester Sulfonate and Propylene Glycol). The second mixture of Sophorolipid (biosurfactant) and Coco Glucoside (Anionic surfactant), this mixture is also called bio-based biodispersant formulation. The emulsification index of the mixture of Sophorolipid and chemical dispersant was 28.46% and the mixture of Sophorolipid and Coco Glucoside had a better emulsification index of 36.59% in emulsifying crude oil. The average effectiveness of the dispersion of the mixture of Sophorolipid and Coco Glucoside is 44.65% and the level of reduction in TPH levels in crude oil with a mixture of Sophorolipid and Coco Glucoside and a consortium of petrophilic bacteria (KBP) within five days of observation is 68.35% with the final bacterial count which counted 1.033x109 cells/mL. The mixture of Sophorolipid and Coco Glucoside had the highest germination index value compared to other test materials of 97.65%. The mixture of Sophorolipid and Coco Glucoside can be used as a mixture of biodispersant formulations which have a high level of biodegradation and safe for the environment.